ANALISIS PIUTANG TAK TERTAGIH DAN PERPUTARAN PIUTANG PADA PT AGUNG SERAYA MOTOR - Mia Rapiana; Puspita Rama Nopiana (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
Accounts receivable is an important matter in the company because it can result in uncollectible accounts receivable, which can result in losses for the company. This research is to determine the analysis of bad debts, accounts receivable receivables, and accounts receivable control. This type of research is quantitative, the data used are secondary and primary data, namely accounts receivable reports, as well as arrears reports in 2017-2019, data collection techniques are documentation and interviews. The data analysis method used in this research is qualitative. The research results show that the average ratio of arrears in 2017-2018 is 13%, and the average collection ratio is 87%, the average receivable ratio is 1.07, the average age of accounts receivable is 387 days.